Effect of Isothiocyanate Therapy on Apoptosis of Trophoblast Cells in Pregnant Rats Hyperglycemia Atmosphere - Harry Kurniawan Gondo; Elizabteh Haryanti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: One of the factors that influence the complications of pregnancy and childbirth is diabetes mellitus. In this study, it was intended to create experimental diabetic conditions in experimental white rats with the administration of aloksan for 5 days. A total of 30 mice were checked for sugar levels on day 7 after inducing alloxane to see that the mice were already in a hyperglycemic state. Then divided into 6 groups, each group there are 5 white pregnant rats. Group 1 was the negative group (without being given aloksan), group 2 was positive group (given aloksan as much as 150 mg / day / kg BB), groups 3, 4, 5 and 6 were given Aloksan 150mg / day / kg and each was given simultaneously isothiocyanates with a dose of 0.1; 0,2; 0.4 and 0.8 mg/day/kg BB. DNA fragmentation is one of the characteristics of apoptosis. In this study DNA fragmentation was examined by the TUNEL method (Terminal deoxynucleotidyl Transferase-mediated dUTP Nick End Labeling). The average number of trophoblast cells in white pregnant rats hyperglycemia that experienced apoptosis decreased as the dose of isotiocyanate therapy increased in rats that had been induced by alloxane. And the best dose is at a dose of 0.8 mg / day / kg BB.